A monopole super wideband microstrip antenna with band-notch rejection - Oskouei, Hamidreza Dalili; Mirtaheri, Alireza (PIERS - FALL : 2017 Progress in Electromagnetics Research Symposium - Fall : 19-22 November 2017, Singapore, 2017)
A novel of monopole antenna withband-notched rejection is presented in this letter. The antenna is include: modifying radiation patch, 50-Ω tapered feed line and defected ground to improve the antenna characteristics. The proposed antenna can be used for the superwide-band (SWB) and ultra-wideband applications. The antenna bandwidth is from 3 to 50 GHz for VSWR < 2. Radiation patterns are omni-directional on UWB spectrum. A rectangular slot on the patch antenna is carved to remove wireless local area network system (WLAN).